Interleukin 35 may contribute to the loss of immunological self‐tolerance in patients with primary immune thrombocytopenia. (29th January 2015) - Sun, Tiantian; Zhang, Donglei; Yang, Yanhui; Zhang, Xian; Lv, Cuicui; Fu, Rongfeng; Lv, Mingen; Liu, Wenjie; Chen, Yunfei; Liu, Wei; Huang, Yueting; Xue, Feng; et al.
Summary Primary immune thrombocytopenia (ITP) is an autoimmune disorder. Interleukin‐35 (IL35) can suppress T cell proliferation and elicit the development of inducible regulatory T cells (Tregs). Previous studies have shown decreased plasma IL35 levels and dysfunctional T cells in patients with ITP. In this study, we determined whether decreased IL35 levels correlate with T cell dysfunction in ITP patients. Plasma IL35 levels were found to be lower in ITP patients than in healthy controls, were positively correlated with platelet levels and the percentage of peripheral circulating Tregs, and negatively correlated with the levels of T helper‐1 cells in ITP patients. We also evaluated the effects of IL35 on cytokines contributing to T cell proliferation. IL35 promoted the secretion of interleukin 10 (IL10) and transforming growth factor–β1 but reduced the levels of interferon‐γ and IL17A (also termed IL17). Moreover, IL35 inhibited the proliferation of CD4+ and CD8+ T cells but induced the differentiation and proliferation of Tregs in ITP. In summary, IL35 appears to contribute to the loss of immunological self‐tolerance in ITP patients by modulating T cells and immunoregulatory cytokines.